IMPRESSION MANAGEMENT FOR DIGITAL CORPORATE IMAGE - Yulianne Safitri; Lidya Wati Evelina (Bina Nusantara University, 2018)
The official account of corporate social media is one tool in delivering campaign messages on social media through brand communication. Usually, the official account content of social media is made to attract public awareness about the company. This study aims to determine the impression of official social media accounts of service companies in Indonesia by usingthe concept of impression management in shaping digital corporate image. The research method used in this research is descriptive qualitative method. Primary data is collected by case study methods, observing the official YouTube account of telecommunications services and e-commerce services in Indonesia. The collected data is analyzed by reducing data, selecting data and categorizing the data obtained in accordance with the research objectives. The data validation used in this study is source triangulation, by interviewing social media practitioners to explore their opinions on how companies create content to form a certain impression. The results of this study show effective strategies that can be done to manage impressions on corporate social media accounts that can be applied in Indonesia. The research findings are known that impression management on corporate social media accounts can create digital corporate image, and the most effective social media platform for managing impression is YouTube, becausethe content in YouTube videos can have social value in life that is close to people's daily lives.